In Situ Wire Drawing of Phosphate Glass in Polymer Matrices for Material Extrusion 3D Printing - J. Gilberto Siqueiros; David A. Roberson (International Journal of Polymer Science)
A strategy to increase the amount of materials available for additive manufacturing platforms such as material extrusion 3D printing (ME3DP) is the creation of printable thermoplastic composites. Potential limiters to the incorporation of filler materials into a thermoplastic resin include agglomeration of the filler materials, which can compromise the mechanical properties of the material system and a static morphology of the filler material. A potential solution to these issues is the use of filler materials with low glass transition temperatures allowing for a change in morphology during the extrusion process. Here, we successfully demonstrate the drawing of phosphate glass particles into a wire-like morphology within two polymeric systems: (1) a rubberized acrylonitrile butadiene styrene (ABS) blend and (2) polylactic acid (PLA). After applying a normalization process to account for the effect of air gap within the 3D printed test specimens, an enhancement in the mechanical properties was demonstrated where an increase in strength was as high as 21% over baseline specimens. Scanning electron microanalysis was used to characterize the fracture surface and wire drawing efficacy. Factors affecting the ability to achieve wire drawing such as polymer viscosity and print temperature are also highlighted.